Surgical morbidity and mortality in patients after microvascular reconstruction for head and neck cancer. (15th November 2017) - Joo, Y‐H.; Cho, K‐J.; Park, J‐O.; Kim, S‐Y.; Kim, M‐S.
Abstract : Objectives: The aim was to evaluate the importance of clinical factors in the prediction of postoperative complications in patients with microvascular reconstruction for head and neck squamous cell cancer (HNSCC). Design: A retrospective review of case notes was performed. Setting: Patients treated at a single institute. Participants: This study included 259 patients with HNSCC treated with radical surgery and microvascular reconstruction between 1993 and 2014. Main outcome measures: We allocated the patients to three groups using a preoperative comorbidity score based on risk factors: group A (≥3 risk factors, n = 16), group B (2 risk factors, n = 49) and group C (0 or 1 risk factor, n = 194). Results: Surgical mortality in this cohort was 1.9% (5 of 259 patients). The preoperative comorbidity score was associated with surgical mortality ( P < .001). Pharyngocutaneous fistula ( P = .001) and flap compromise ( P = .023) were more frequent as preoperative comorbidity score increased. Preoperative comorbidity score ( P < .001), advanced age ( P = .007), advanced pathologic T stage ( P = .028), advanced pathologic N stage ( P = .005), preoperative (chemo) radiotherapy ( P < .001), history of cardiovascular disease ( P = .015) and pulmonary disease ( P = .007), and diabetes (P < .001) had significant adverse effects on 5 year disease‐specific survival (DSS) in a univariate analysis. The 5‐DSS rates of groups A, B and C were 30%, 37% and 70%, respectively. Multivariate analysis showed that preoperative comorbidity score was significantly correlated with 5 year DSS (hazard ratio [HR], 3.56; 95% confidence interval [CI], 1.81—6.99; P < .001 for group A and HR, 1.91; 95% CI, 1.15—3.18; P = .013 for group B compared with group C). Conclusion: Patients with a high preoperative comorbidity score have an increased risk of surgical mortality and morbidity after microvascular reconstruction for HNSCC.